2022
DOI: 10.1126/scisignal.abn4948
|View full text |Cite
|
Sign up to set email alerts
|

Fusobacterium nucleatum induces proliferation and migration in pancreatic cancer cells through host autocrine and paracrine signaling

Abstract: The tumor microbiome is increasingly implicated in cancer progression and resistance to chemotherapy. In pancreatic ductal adenocarcinoma (PDAC), high intratumoral loads of Fusobacterium nucleatum correlate with shorter survival in patients. Here, we investigated the potential mechanisms underlying this association. We found that F. nucleatum infection induced both normal pancreatic epithelial cells and PDAC cells to secrete increased amounts of the cytokines GM-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 82 publications
3
38
0
1
Order By: Relevance
“…Moreover, F. nucleatum enhances the secretion of pro-inflammatory cytokines, such as cyclooxygenase-2, interleukin (IL)-8, IL-6, IL-1ß, and tumor necrosis factor alpha (TNF-α) [39]. Similar results were found in pancreatic cancer, when both infected normal and pancreatic cancer cells secreted increased amounts of the cytokines Granulocyte-macrophage colony-stimulating factor, C-X-C motif ligand 1 (CXCL1), IL-8, and MIP-3α, known to increase proliferation, migration, and invasive cell motility [40 ▪ ]. Also, F. nucleatum can induce inflammation in CRC cells by promoting the production of reactive oxygen species (ROS) [41].…”
Section: Fusobacteria In (Oral) Cancermentioning
confidence: 56%
“…Moreover, F. nucleatum enhances the secretion of pro-inflammatory cytokines, such as cyclooxygenase-2, interleukin (IL)-8, IL-6, IL-1ß, and tumor necrosis factor alpha (TNF-α) [39]. Similar results were found in pancreatic cancer, when both infected normal and pancreatic cancer cells secreted increased amounts of the cytokines Granulocyte-macrophage colony-stimulating factor, C-X-C motif ligand 1 (CXCL1), IL-8, and MIP-3α, known to increase proliferation, migration, and invasive cell motility [40 ▪ ]. Also, F. nucleatum can induce inflammation in CRC cells by promoting the production of reactive oxygen species (ROS) [41].…”
Section: Fusobacteria In (Oral) Cancermentioning
confidence: 56%
“…In addition, NF-κB plays an important role in regulating the survival, activation and differentiation of immune cells. Of particular interest, this signaling pathway is involved in promoting cell proliferation and closely related to cancer development and progression, of which is promotion of proliferation of pancreatic ductal adenocarcinoma (PDAC) and colorectal cancer [ 129 , 131 ] ( Figure 3 ).…”
Section: Virulence Factors Of Periodontal Pathogens and Their Associa...mentioning
confidence: 99%
“…Udayasuryan et al found that F. nucleatum infection increased the secretion of granulocyte-macrophage colony-stimulating factor (GM-CSF), CXCL1, IL-8, and macrophage inflammatory protein 3α, which could contribute to the accumulation of MDSCs in the TMA. It could be that GM-CSF promotes the proliferation of pancreatic cancer cells [ 2 , 51 ]. In addition, the inflammasome PRR is involved in the formation of a protein complex that activates inflammatory pathways through the recognition of PAMPs or DAMPs by associated receptors, and inflammasome defects cause inflammation-induced colorectal cancer [ 4 ].…”
Section: Mechanism Of the Role Of Intra-tumorigenic Bacteria In Tumor...mentioning
confidence: 99%